Which birds have the most to lose? an analysis of bird species’ feeding habitat in changing Australian landscapes - Carly E. Campbell; Darryl N. Jones; Monica Awasthy; J. Guy Castley; Alienor L.M. Chauvenet (Biodiversity and Conservation, 2024)
Australia has lost vast areas of its natural vegetation through agriculture and urbanization, resulting in the area of suitable habitat for many Australian bird species being greatly diminished. Given the geographical and ecological biases in anthropogenic land use, the impact of habitat loss now and into the future may be disproportionately high for some species, threatening their long-term persistence. Such changes are occurring rapidly, and habitat loss needs to be monitored dynamically to prevent extinction. To monitor changes in available unmodified species habitat, we use species’ area of feeding habitat (AFH), which represents the area of habitat within a species’ range with vegetation matching their feeding requirements. We analysed the past, current and future threats of habitat modification for 467 Australian bird species by calculating AFH across three time periods: pre-colonization, current (2020), and a projected future scenario (2100). These values were used to identify species subject to substantial habitat loss due to urbanization and agriculture and delineate predictors of such losses. Most species had experienced habitat loss since colonization ( n = 442, 95%), and species that had already experienced considerable habitat loss were more likely to lose habitat into the future. Species with particular habitat associations (e.g., Mallee), were also more prone to greater proportions of habitat lost. The results highlight the utility of AFH and emphasize the importance of protecting what habitat remains for the species with highly depleted geographic ranges, noting that those that have experienced the most loss of unmodified habitat are the most likely to lose more unmodified habitat under future conditions.

How do we study birds in urban settings? A systematic review - Carly E. Campbell; Darryl N. Jones; Monica Awasthy; Alienor L. M. Chauvenet (Biodiversity and Conservation, 2022)